Policy Evaluation of Legal Aid for the Poor in Tangerang Attribution-ShareAlike 4.0 International (CC BY-SA 4.0) Regency - Bachtiar Bachtiar (International Journal of Social Service and Research, 2023)
This research is motivated by the fact that since 2016 the Government of Tangerang Regency has established a policy for administering legal aid which is formalized in the Regional Regulation of Tangerang Regency Number 14 of 2016 concerning the Implementation of Legal Aid. Even though a policy on the provision of legal aid has been presented and implemented in the framework of protecting the rights of the poor person or group of people in Tangerang Regency, the implementation of this policy needs to be evaluated, to find out the effectiveness, efficiency, equity, adequacy responsiveness, and appropriateness of the community to the policy. The aims and objectives of this research are to find out and analyze the current implementation of the policy of providing legal aid for the poor in Tangerang Regency, as well as to find out, analyze and find the ideal implementation of the policy of providing legal aid for the poor in Tangerang Regency in the future. This study was designed in the realm of qualitative research using the constructivism paradigm, using two types of data, namely: primary data and secondary data, and the determination of informants was carried out using a purposive sampling technique. The data obtained is tested using the policy evaluation model from William Dunn which includes the criteria; effectiveness, efficiency, adequacy equity, responsiveness, and appropriateness policy. The results of the study show that the implementation of legal aid policies in Tangerang Regency has not been fully effective. Going forward, the implementation of legal aid policies in Tangerang Regency needs to be designed as responsive policies, namely policies made and implemented by considering and considering the needs, hopes and desires of the community. In the future, the implementation of legal aid policies must pay attention to several important matters, such as accessibility, effectiveness, efficiency, coordination and cooperation. Apart from that, the implementation of the legal aid policy also requires several important things, including: provision of adequate resources; continuous monitoring and evaluation; effective coordination with other stakeholders; community education and sensitization; and adequate financial support.